Taḥqīq Mafhūm al-Istiṭā‘ah al-Ṣiḥḥiyyah li al-Ḥujjāj al-Ṭābūrīn fī Indūnīsiyā al-Mu‘āṣirah - Suhaili Sufyan, Muhammad; Abu Bakar, Ali; Mubarrak, Husni; Munir, Badrul; Yunus, Saifullah (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2024)
Hajj is a pillar of Islam, obligatory for every Muslim who is financially and physically capable. This research focuses on the health condition as a key requirement for performing Hajj in Indonesia, particularly for pilgrims in long queues. Ensuring health and safety before, during, and after Hajj has become a critical aspect, mandated by Islamic law and Indonesian regulations. The condition of health and the ability to provide food and equipment, constitutes a fundamental part of the